Assessment of Collective Unconscious Mental State & Female Feticide in India - Harish Kumar Sharma (Research Developments in Arts and Social Studies Vol. 1, 2022)
Normally every human behavior is linked to the individual mental state but some behaviors that involve large number of people can be explained with Collective mental State. This collective mental state is constructed on the basis of long historical experiences, so it is usually unconscious. Collective Unconscious is a concept given by Carl Jung. The collective unconscious is also known as "a reservoir of the experiences of our species." It refers to the retaining of ancestral experiences at unconscious which are transferred from one generation to other generation in a long course of life. Jung stated that it ranges from retaining passive record of historical experiences i.e. passive Repository the actual practical emergence in ground reality i.e. Active Substratum. The female feticide occurring at mass level in India seems to be a reflection of Substratum state of collective unconscious. It means the historical experiences that are retained in collective unconscious at passive repository unconscious state has acquired the active substratum state of collective unconscious. These experiences are specifically related to the invasions people experienced during medieval period. This link is strengthened when the female sex ratio in India is observed state wise. Female feticide is highest in North-West states and lowest in Southern states. It means that the active substratum state of collective unconscious is the strongest causative factor of female feticide in India.